Consolidative Chemoradiotherapy After Induced Chemotherapy Is an Optimal Regimen for Locally Advanced Pancreatic Cancer - Wu, Lili; Zhou, Yuhong; Fan, Yue; Rao, Shengxiang; Ji, Yuan; Sun, Jing; Li, Tingting; Du, Shisuo; Guo, Xi; Zeng, Zhaochong; Lou, Wenhui (Frontiers in Oncology, 2020)
Object: To evaluate the efficacy and tolerability of consolidative chemoradiotherapy (cCRT) after induced chemotherapy (iCT) for locally advanced pancreatic cancer (LAPC). Patients and Methods: Patients with LAPC were enrolled from January 2013 to November 2018. In stage one, all patients received iCT. Those without disease progression proceeded to stage two, received 50.4 Gy cCRT with S-1 as radiosensitizer. Efficacy and tolerability were evaluated in all patients. Results: 65 patients enrolled into this study and accepted iCT. 11 (16.9%) patients got early progressions or declined general condition, 1(1.5%) patient quit the trial after 1 cycle of iCT. These 12 patients didn’t receive cCRT. The remaining 53(81.5%) patients received cCRT. After cCRT, 4 of 53(7.5%) patients accepted radical resection. The treatment was well tolerated. In stage one, neutropenia and thrombocytopenia were the most frequent toxicities, the severe toxicity (grade 3 and 4) were 26.2% and 20.0% respectively. In stage two, fatigue (45.3%) and nausea (41.5%) were the most frequent toxic effects but most were mild. The median overall survival (OS) of whole group was 18.1 months [95% CI, 15.11-21.03 months]. The OS of patients with early progression and patients accepted cCRT were 7.6 months [95%CI, 5.22-10.02 months] and 19.5 months [95% CI, 18.08-20.95 months] respectively (P＜0.001). The PFS of the 53 patients was 10.3 months [95% CI, 8.54-12.0 months] and survival rates at 1- and 2- years were 84.8% and 24.3%, respectively. Conclusion: The current results indicate that iCT is a useful screening method to selecting LAPC patients with less-aggressive biological behavior. cCRT after iCT in patients with LAPC is an optimal treatment. The prognosis of patients who received complete treatment is significantly improved.